Proposal of rebar welding works connected to plate of steel column of BRAC University new campus project - BUCG-ABC Joint Venture (Brac University, 2023)
This record consists of general correspondence regarding proposal of rebar welding works connected to plate of steel column of BRAC University new campus project.